Ответы и объяснения

2013-08-21T16:09:49+00:00
1). 2x^{2}+7x-4=x^{2}-4(x+4)

2x^{2}+7x-4=x^{2}-4x-16

x^{2}+11x+12=0

 x_{1}=-12; x_{2}=1

Сумма корней = -11.

2). 3(x+4)^{2}+5|x+4|-2=0

t=|x+4|

3t^{2}+5t-2=0

D=25+4*6=49

 t_{1} = \frac{-5-7}{6} <0 не удовл., т.к. модуль не может быть отриц. числом

 t_{2} = \frac{-5+7}{6} = \frac{1}{3}

|x+4|= \frac{1}{3}

x+4 =  \frac{1}{3} или x+4 = - \frac{1}{3}

x=- \frac{11}{3} или x=- \frac{13}{3}

Сумма корней = - \frac{11}{3}-  \frac{13}{3} =- \frac{24}{3}=-8

Ответ: -8.